Occurrence patterns of crop‐foraging sika deer distribution in an agriculture–forest landscape revealed by nitrogen stable isotopes. Issue 21 (11th October 2021) - Hata, Ayaka; Nakashita, Rumiko; Fukasawa, Keita; Minami, Masato; Fukue, Yuko; Higuchi, Naoko; Uno, Hikaru; Nakajima, Yasuhiro; Saeki, Midori; Kozakai, Chinatsu; Takada, Mayura B.
Abstract: Conflicts arising from the consumption of anthropogenic foods by wildlife are increasing worldwide. Conventional tools for evaluating the spatial distribution pattern of large terrestrial mammals that consume anthropogenic foods have various limitations, despite their importance in management to mitigate conflicts. In this study, we examined the spatial distribution pattern of crop‐foraging sika deer by performing nitrogen stable isotope analyses of bone collagen. We evaluated whether crop‐foraging deer lived closer to agricultural crop fields during the winter and spring, when crop production decreases. We found that female deer in proximity to agricultural crop fields during the winter and spring were more likely to be crop‐foraging individuals. Furthermore, the likelihood of crop consumption by females decreased by half as the distance to agricultural crop fields increased to 5–10 km. We did not detect a significant trend in the spatial distribution of crop‐foraging male deer. The findings of spatial distribution patterns of crop‐foraging female deer will be useful for the establishment of management areas, such as zonation, for efficient removal of them. Abstract : We examined the spatial distribution pattern of crop‐foraging sika deer by performing nitrogen stable isotope analyses. Female deer in proximity to agricultural crop fields were more likely to be crop‐foraging individuals and the likelihood of crop consumption decreased by half as the distance to agricultural crop fields increased to 5–10 km.